Quantifying Geodetic Mass Balance of the Northern and Southern Patagonian Icefields Since 1976 - McDonnell, Morgan; Rupper, Summer; Forster, Richard (Frontiers in Earth Science, 2022)
Southern Andean glaciers contribute substantially to global sea-level rise. Unfortunately, mass balance estimates prior to 2000 are limited, hindering our understanding of the evolution of glacier mass changes over time.. Elevation changes over 1976/1979 to 2000 derived from historical KH-9 Hexagon imagery and NASADEM provide the basis for geodetic mass balance estimates for subsets of the Northern Patagonian Icefield (NPI) and the Southern Patagonian Icefield (SPI) , extending current mass balance observations by ~20 years. Geodetic mass balances were -0.63 ± 0.03 m w.e. yr-1 for 63% of the NPI and -0.33 ± 0.05 m w.e. yr-1 for 52% of the SPI glacierized areas for this historical period. We also extend previous estimates temporally by 25% using NASADEM and ASTER elevation trends for the period 2000 to 2020, and find geodetic mass balances of -0.86 ± 0.03 m w.e. yr-1 for 100% of the NPI and -1.23 ±0.04 m w.e. yr-1 for 97% of the SPI glacierized areas. 2000 to 2020 aggregations for the same areas represented in the 1976/1979 to 2000 estimate are -0.78 ± 0.03 m w.e. yr-1 in the NPI and -0.80 ± 0.04 m w.e. yr-1 on the SPI. The significant difference in SPI geodetic mass balance in the modern period for 100% versus 52% of the glacierized area suggests subsampling leads to significant biases in regional mass balance estimates. When we compare the same areas in each time period, the results highlight an acceleration of ice loss by a factor of 1.2 on the NPI and 2.4 on the SPI in the 21st century as compared to the 1976/79 to 2000 period. While lake-terminating glaciers show the most significant increase in mass loss rate from 1976/1979-2000 to 2000-2020, mass balance trends are highly variable within glaciers of all terminus environments, which suggests that individual glacier sensitivity to climate change is dependent on a multitude of morphological and climatological factors.